Comparison of Bupivacaine and Dexmedetomidine versus Bupivacaine Alone in Transversus Abdominis Plane Block for Post-Operative Analgesia - Aftab Hussain, Akhtar Hussain, Rehana Feroze, Muhammad Akram, Muhammad Asif Saleem, Ahsan Ali, Aftab Hussain, Akhtar Hussain, Rehana Feroze, Muhammad Akram, Muhammad Asif Saleem, Ahsan Ali (Journal of Rawalpindi Medical College, 2021)
Objective: To study the effects of adding dexmedetomidine to bupivacaine in transverses abdominis plane block in comparison with using bupivacaine alone. Materials and Methods: This was a prospective comparative study that was conducted in the Anaesthesia Department, CMH, Lahore over a period of six months from 1st June 2020 to 30th November 2020. Fifty patients of the American Society of Anesthesiologist Class I and II with an age range between 40 to 60 years were divided into two groups. Group B received 20ml of 0.25% bupivacaine with 2ml of normal saline on each side in the transversus abdominis plane block while group BD was given 20ml of 0.25% bupivacaine with dexmedetomidine 0.5mcg/kg on each side (in a volume of 2ml). Post-operative pain was assessed with a visual analogue scale. Rescue analgesia was given when a score of greater than 3 was observed using this scale. Time to first rescue analgesia was noted. Total opioid consumption in the first 24 hours was also recorded. Patients were observed for postoperative hypotension and bradycardia. Results: The mean-time for the first dose of analgesia for group B and BD was 302.92 ± 24.01 and 419.28 ± 31.97 minutes respectively with a p-value of 0.001. The mean of the total consumption of opioids in 24 hours post-operatively for group B and BD was 14.20±2.36 and 10.40±1.38 mg respectively with a p-value of 0.001. Hypotension was not seen in any patient in either group. Only one patient developed bradycardia and he belonged to group BD. P-value was 0.327. Conclusion: The addition of dexmedetomidine to bupivacaine for transversus abdominis plane block for postoperative analgesia significantly prolongs the duration of analgesia and reduces the postoperative opioid requirements.